Influence of legacy disturbance on functional connections between geomorphology and organic matter dynamics in mountain streams - Ruffing, Claire Marie (Kansas State University, 2014)
Geomorphic properties of streams are linked to ecosystem function through processes related to storage, transport, and other drivers regulating biogeochemical conditions. Disturbances altering the physical template of a stream are associated with cascading impacts on ecosystem function. However, few disturbances are studied at long time scales and so the legacy of such events and the implications for ecosystem structure and function are not well understood. This research investigates the role of historic tie-driving, a channel disturbance legacy, in shaping present-day stream channel conditions in the Rocky Mountain region and the associated implications for organic matter dynamics. Using a combination of geomorphic and riparian surveys, organic matter and vegetation sampling, and modeling, I show that components of mountain stream ecosystems have recovered from tie-driving at varying rates. First, I addressed how tie-driving has altered channel morphology and wood loading. Tie-driven streams are narrower, shallower, less rough, and have less wood than non-driven reference reaches. In a second study, I focused on differences in carbon storage within the stream and riparian area between tie-driven and non-driven streams. Carbon stored on the landscape represents a long-term component of the terrestrial carbon cycle and some, but not all, components have been impacted by tie-driving. Large instream wood, coarse downed wood, and fine downed wood were identified as carbon storage components that were significantly smaller in tie-driven stream-riparian corridors. Finally, I modeled whole stream ecosystem metabolism and tested whether abiotic drivers influenced variations in rates of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem productivity (NEP). Results from this work suggest that rates of GPP were significantly different between tie-driven and non-driven streams and were partially explained by variations in light related to canopy structure. However, variations in ER and NEP were not significantly different between tie-driven and non-driven sites. Taken as a whole, this work shows that ecosystems bear the imprint of historic disturbances but individual ecosystem components recover at differing rates. Additionally, integrating stream hydro-geomorphic and ecological dynamics is an effective approach to understanding the impact of channel disturbances in shaping ecosystem function at a variety of spatial and temporal scales.
Keywords: Streams; Disturbance; Geomorphology; Freshwater ecology; Ecology (0329); Fisheries and Aquatic Sciences (0792); Geography (0366)